Machine‐Driven Chemoenzymatic Synthesis of Glycopeptide. Issue 45 (31st August 2020) - Zhang, Jiabin; Liu, Ding; Saikam, Varma; Gadi, Madhusudhan R.; Gibbons, Christopher; Fu, Xuan; Song, Heliang; Yu, Jin; Kondengaden, Shukkoor M.; Wang, Peng G.; Wen, Liuqing
Abstract: Historically, researchers have put considerable effort into developing automation systems to prepare natural biopolymers such as peptides and oligonucleotides. The availability of such mature systems has significantly advanced the development of natural science. Over the past twenty years, breakthroughs in automated synthesis of oligosaccharides have also been achieved. A machine‐driven platform for glycopeptide synthesis by a reconstructed peptide synthesizer is described. The designed platform is based on the use of an amine‐functionalized silica resin to facilitate the chemical synthesis of peptides in organic solvent as well as the enzymatic synthesis of glycan epitopes in the aqueous phase in a single reaction vessel. Both syntheses were performed by a peptide synthesizer in a semiautomated manner. Abstract : An automation platform was designed for glycopeptide synthesis. The automation process is based on chemoenzymatic synthesis and the use of a silica resin and a commercially available peptide synthesizer. The system performs chemical synthesis of peptide in organic solvent, and enzymatic synthesis of glycan epitopes in the aqueous phase using the silica gel resin.